Stališča staršev do nacionalnega preverjanja znanja ob koncu drugega vzgojno-izobraževalnega obdobja - Škalič, Mateja (Revija za elementarno izobraževanje, 2017)
The article presents parents' views on the National Assessment of Knowledge at the end of the second educational cycle of basic school. In more detail we present the views of parents on the necessity of the National Assessment of Knowledge and on encouraging children to prepare for it. In the theoretical part we define assessments and further present The National Assessment of Knowledge. We then proceed to present the results of a survey conducted in 2014. The study involved 209 parents of pupils in the 6th grade from the Podravje and Pomurje regions. The survey results show that the child's accomplishment at the National Assessment of Knowledge provides good feedback for the parents regarding the child's knowledge, however, they also believe it does not show a comprehensive overview of knowledge. Parents who have completed basic school and parents who live in the Pomurje region attribute a more prominent role in encouraging children to prepare for The National Assessment of Knowledge to the teachers, rather than to themselves. The survey results alert us to the fact that in terms of parents' involvement children from the Pomurje region live in a less stimulating environment.
Keywords: nacionalno preverjanje znanja; national assessment of knowledge; parents; starši; second educational period; stališča; osnovne šole; Podravje region; Podravska regija; Pomurje region; Pomurska regija